PADA HUBUNGAN ANTARA PERSEPSI, JENIS KELAMIN, STATUS TEMPAT TINGGAL, STATUS ORANG TUA DENGAN PERILAKU PENYALAHGUNAAAN NAPZA PADA KELAS XI DI SMK DARUL HUDA SIDOARJO (UNUSA Press, 2018)
Abstract: Adolescence signify of transition from childhood to adulthood is easy to having psychologyand behavior problems, such as learning difficulty, anxiety, and drug addiction. School children asvulnerable group in drugs abuse behavior. The impact of drug abuse particularly alternately needle useget risk infection disease such as hepatitis B, C, and HIV. The objective of this research to examines thecorrelation between perception, sex, domicile status, parent status with drugs abuse behavior. This studyused cross sectional analytical design with simple random sampling technique. Population of theresearch are students of 155 individuals, sample with 50 respondents. Data analysis employed chisquare test. The result indicates that 83,7% having drugs abuse behavior with statistic test found thereare no correlation between perception ( value = 0,826) and drugs abuse behavior, and foundcorrelation between sex ( value = 0,001), domicile status relationship ( value = 0,001),parent statusrelationship ( value = 0,025), with drugs abuse behavior. Good communication among familymembers able to providing protection to child in order to avoid from drugs abuse. Good perceptionabout drugs, stay with complete parents and in harmony has correlation to drugs abuse prevention.